Combining ability analysis in bread wheat (Triticum aestivum (L.) Em. Thell) under different environmental conditions - Sharma, Vijay; Dodiya, NS; Dubey, RB; Khan, Rumana (Bangladesh Journal of Botany, 2019)
Pooled analysis of 8 genotypes of wheat of diverse origin, their 28 F1s and 2 checks was carried out in 4 different environments to study the combining ability in bread wheat for grain yield and its component traits. On pooled basis, analysis of variance due to GCA and SCA was significant for all characters revealed difference between parents for GCA and difference between crosses for SCA. Similarly, mean square due to GCA × E was significant for number of effective tillers per plant and flag leaf area revealed influence of environment on GCA. Whereas SCA × E was also significant for number of effective tillers per plant and grain yield per plant revealed influence of environment on SCA. The variance due to GCA was higher than their respective SCA for all characters except number of grains per spike indicating that additive type of gene action played role in the expression of all these traits. Significant GCA effects for grain yield and its component traits were exhibited by the parents HD 2987, Lok 1 and HI 1544. Fourteen crosses recorded showed significant SCA effects for grain yield and related traits.